The Carolingian World through Hagiography - Gibson, Kelly (History compass, 2015)
Hagiographic texts - including the lives of saints, accounts of relic translations, miracle collections, and deeds of abbots and bishops - are plentiful and rich sources for investigating the Carolingian world. The recognition that hagiography offers a great deal of information about the author's time has led scholars to use these texts to shed light on a variety of topics. Hagiography's similarity to history as well as literature means that scholarship on history and literature can contribute to our understanding of hagiography and the world that produced it. Works comparing earlier versions of saints' lives with their Carolingian-era revisions and investigating hagiography alongside works of other genres have contributed to some of the biggest debates in Carolingian history: the reform of the church, monasticism, and society; the renaissance of learning, the impact of doctrinal controversies, and views of kingship and reactions to political change.